Operation Himalayas : to defend Indian sovereignty - Sinha, Satyanarayan, 1910- (S. Chand, 1975)
On the activities of the Himalayan Pilots' Association, an Indian guerrilla organization attempting to curb the Chinese influence on the Himalayan front.